Unitary operators with decomposable corners - Andruchow, Esteban (2021)
We study pairs (U, L) , where U is a unitary operator in H and L⊂ H is a closed subspace, such that PL0U|L0:L0→L0has a singular value decomposition. Abstract characterizations of this condition are given, as well as relations to the geometry of projections and pairs of projections. Several concrete examples are examined.